Whistleblower Protection Act 2010: is it in line with UNCAC and UNCAC Implementation Review Group (IRG) and Conference of States Parties (COSP) requirement? - Mohd Ali @ Ramli, Azlin Namili; A. Rahman, Aspalella; Yaacob, Nurli (Global Academic Excellence, 2018)
Corruption is a global phenomenon that continues to hit the world. It does not no any boundaries. Although corruption is caused by variety of reasons, the main tool proposed to prevent and combat corruption is whistleblowing. A member country to the United Nations Convention against Corruption (UNCAC), Malaysia has enacted the Whistleblower Protection Act (APPM 2010) in 2010 in response to the recommendation to (UNCAC). Using the library research method, this paper discusses whether the provisions in APPM 2010 is in line with the UNCAC requirements. It is found that some of the provisions in APPM 2010 are in line with UNCAC, however others are not which may result in ineffectiveness of the Act. At the end of the discussion, recommendation is posted for improvement.